Graph Transformation 8th International Conference, ICGT 2015, Held as Part of STAF 2015, L'Aquila, Italy, July 21-23, 2015. Proceedings - Parisi-Presicce, Francesco; Westfechtel, Bernhard (Theoretical Computer Science and General Issues, 2015)
This book constitutes the proceedings of the 8th International Conference on Graph Transformations, ICGT 2015, held in L'Aquila, Italy, in July 2015. The 15 full papers presented together with 3 short papers and 1 keynote were carefully reviewed and selected from 27 submissions. The papers are organized in topical sections on foundations; applications: technical papers, and tool presentations.